SELECT * FROM question_mgmt as q WHERE id=1153 AND status=1 SELECT id,question_no,question,chapter FROM question_mgmt as q WHERE courseId=3 AND subId=6 AND chapterId=96 and ex_no='2' AND status=1 ORDER BY CAST(question_no AS UNSIGNED)
y = ex +1 : yn -y' = 0
y = ex +1
Differentiating both sides of this equation with respect to x, we get:
\begin{align}\frac{dy}{dx}=\frac{d}{dx}(e^x + 1)\end{align}
=> y' = ex ...(1)
Now, differentiating equation (1) with respect to x, we get:
\begin{align}\frac{d}{dx}(y^{'})=\frac{d}{dx}(e^x)\end{align}
=> y'' = ex
Substituting the values of y' and y'' in the given differential equation, we get the L.H.S. as:
y'' - y' = ex - ex = 0 = R.H.S.
Thus, the given function is the solution of the corresponding differential equation.
Comments
Taking Screenshots on your Samsung Galaxy M31s is very easy and quick.
Report a problem on Specifications:
Taking Screenshots on your Samsung Galaxy M31s is very easy and quick.
Report a problem on Specifications:
Taking Screenshots on your Samsung Galaxy M31s is very easy and quick.
Report a problem on Specifications: